2018
DOI: 10.1186/s12887-018-1308-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of weekly cell phone counselling calls and daily text messages to improve breastfeeding indicators

Abstract: BackgroundEvery year, nearly one million deaths occur due to suboptimal breastfeeding. If universally practiced, exclusive breastfeeding alone prevents 11.6% of all under 5 deaths. Among strategies to improve exclusive breastfeeding rates, counselling by peers or health workers, has proven to be highly successful. With growing availability of cell phones in India, they are fast becoming a medium to spread information for promoting healthcare among pregnant women and their families. This study was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 21 publications
1
68
0
8
Order By: Relevance
“…A study in Nigeria [20] showed that breastfeeding related text messages were effective in improving EBR at six months. Another study in India [21] showed that mobile phone and text message interventions for lactation support improved EBF measured at multiple points of time. Together, these studies suggest that breastfeeding messaging or support offered by mobile phone could potentially be a low cost strategy for improving breastfeeding practices in a variety of settings.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Nigeria [20] showed that breastfeeding related text messages were effective in improving EBR at six months. Another study in India [21] showed that mobile phone and text message interventions for lactation support improved EBF measured at multiple points of time. Together, these studies suggest that breastfeeding messaging or support offered by mobile phone could potentially be a low cost strategy for improving breastfeeding practices in a variety of settings.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized trials indicated mobile phone reminder improves appointment compliance [20,23,24], adherence to ART and Tb medications [25,26]. In addition, it facilitates provision of health education, counseling [27,28] and behavioral change interventions [17,29].…”
Section: Introductionmentioning
confidence: 99%
“…A pilot trial was conducted in four urban maternity hospitals in Nagpur to understand the effectiveness of using mobile phones for personalized lactation counselling and health messaging to promote appropriate IYCF practices. The results demonstrated a positive impact of this intervention on breastfeeding practices and high rates of satisfaction of the women receiving the intervention (Patel et al, ). Subsequently, a formative study was conducted in rural areas similar to the M‐SAKHI trial settings, to understand the use of mobile phones by ASHA workers, ownership and use of mobile phones by pregnant women and their families, the perceptions of pregnant, lactating, and postlactating women about acceptance and utility of text messages regarding health, current dietary, and hygiene practices, and its impact on their health‐seeking behaviour.…”
Section: Methodsmentioning
confidence: 95%
“…Another recently published pilot trial reported significant improvement in breastfeeding practices and pregnancy outcomes in those pregnant women who received text messages and cell phone counselling (Patel et al, ). This pilot trial informed the methods of the current study.…”
Section: Introductionmentioning
confidence: 99%